LOS GOBIERNOS AUT”NOMOS DESCENTRALIZADOS MUNICIPALES Y LA ESTABILIDAD DE LOS TRABAJADORES AL INICIO DE LAS NUEVAS ADMINISTRACIONES - Estupiñan Sosa, Carlos Gianni (2024)
This research addresses the job stability of workers in the Decentralized Autonomous Governments (GAD) at the beginning of new administrations. The preface highlights the importance of a job stability as a fundamental human right and its impact on the social morale of employees. The main objectives include analyzing the current situation of job stability in the GAD, identify violations of workers’ rights, and propose recommendations to improve human resources management. The used methodology is empirical and descriptive, using an analytical approach that combines tools such as surveys and interviews with GAD workers. The results reveal that there is a significant violation of labor rights, with 65% of the respondents reporting untimely dismissals and lack of transparency in the hiring processes at the beginning of new administrations. The political tendency and the preferences of the political parties are the main components for the arbitrary dismissal of public servants belonging to the GAD without any prior report or evaluation. In addition, deficiencies were identified in the application of labor standards which affects worker’s stability. The outcomes highlight the need of implementing more effective policies that guarantee a job stability and protect the rights of workers in the GAD before a new administration, as well as the importance of training the managers in human resources management.